Understanding gendered access and uptake of climate services to develop socially inclusive programming in Kenya - Bullock, Renee; Katothya, Gerald (International Livestock Research Institute, 2022)
Climate information services (CIS) can inform and assist farmers in decision-making processes to manage climate-related risks. However, access and uptake of CIS has been generally low in Kenya. We use qualitative methods to better understand social dimensions of CIS access and uptake in three locations classified as arid and semi-arid (ASALs) counties. We collected information to understand women’s and men’s sources of climate information, perceptions of access and reliability, and decision-making processes. We also solicited recommendations from FGD members and generated guidelines to inform the development of more socially inclusive climate services and a strategy for implementation in 2023. We suggest developing more inclusive co-production processes by increasing collaboration with climate service providers and tailoring content for women and youth in pastoralist contexts. Recommendations to support CIS access and uptake in local communities include developing more CIS dissemination channels, expanding learning networks, facilitating access to resources and increasing women’s agency in CIS uptake.